The Urban versus the Bedouin in the Image of Ruins in Pre-Islamic Poetry - Alzoubi, Mohammad; Ayyat, Hamed (Dirasat: Human and Social Sciences, 2021)
The fear of losing the cultural identity reflected in the ruins of wrecked places and entities was one of the most important problems that faced Pre-Islamic poets in their attitudes towards ruins as these material debris symbolizes their psychological sense of wreckage where it comes to their own history and culture. To face the extinction of such wreckage, Pre-Islamic poets resorted to endorsing the lost identity of this wreckage through naming, locating and describing it in detail. In this way, the poet describes his portrays as tattoos and scripts, hoping to gain immortality and resist all the factors which leading to extinction. Since tattooing was a purely Bedouin image related to magical pagan beliefs and as writing was a purely civilized picture as indicated in this research, the two researchers find it most likely that there are two different reactions to the possible in facing the cultural extinction in question on part of Pre-Islamic poets. These were (1) a traditional emotional Bedouin response that sticks to the idea of belonging to a pagan culture with its Pre-Islamic lifestyle that depends on maintaining culture in the form of oral narrative. And (2) a new rational civilized response that advocates the necessity of maintaining the traditional culture through writing. This last response requires the adoption of the tools and means of civilization, thus and transforming from the stage of Bedouin life to the stage of urban civilization.